2012
DOI: 10.1007/s00382-012-1463-4
|View full text |Cite
|
Sign up to set email alerts
|

Decadal and long-term sea level variability in the tropical Indo-Pacific Ocean

Abstract: International audienceIn this study, we analysed decadal and long-term steric sea level variations over 1966-2007 period in the Indo-Pacific sector, using an ocean general circulation model forced by reanalysis winds. The simulated steric sea level compares favourably with sea level from satellite altimetry and tide gauges at interannual and decadal timescales. The amplitude of decadal sea level variability (up to ~5 cm standard deviation) is typically nearly half of the interannual variations (up to ~10 cm) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
130
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 127 publications
(137 citation statements)
references
References 89 publications
7
130
0
Order By: Relevance
“…It thus fits Douglas's [1991] criterion of >60 years and Houston and Dean's [2013] criterion of >75 years for the reliable estimation of MSL trends and accelerations, respectively, though interannual and decadal variability of MSL remains problematic along the Western Australian coast [e.g., Amin, 1993;Nidheesh et al, 2013]. Nevertheless, the length of the FREM record means that it has been used in many global and regional sea level assessments [e.g., Holgate and Woodworth, 2004;Fenoglio-Marc and Tel, 2010;Bouin and W€ oppelmann, 2010;Houston and Dean, 2012;Burgette et al, 2013, as well as the references cited earlier].…”
Section: The Fremantle Tg and Previous Vlm Estimatesmentioning
confidence: 85%
See 1 more Smart Citation
“…It thus fits Douglas's [1991] criterion of >60 years and Houston and Dean's [2013] criterion of >75 years for the reliable estimation of MSL trends and accelerations, respectively, though interannual and decadal variability of MSL remains problematic along the Western Australian coast [e.g., Amin, 1993;Nidheesh et al, 2013]. Nevertheless, the length of the FREM record means that it has been used in many global and regional sea level assessments [e.g., Holgate and Woodworth, 2004;Fenoglio-Marc and Tel, 2010;Bouin and W€ oppelmann, 2010;Houston and Dean, 2012;Burgette et al, 2013, as well as the references cited earlier].…”
Section: The Fremantle Tg and Previous Vlm Estimatesmentioning
confidence: 85%
“…This is more challenging than using geodetic-only techniques because of interannual and decadal sea level variability due to a strong El Nino Southern Oscillation signal along the Western Australian coast [e.g., Amin, 1993;Nidheesh et al, 2013], and additional uncertainty of radar altimetry close to the coasts [e.g., Deng et al, 2002].…”
Section: Differential Rlr and Altimetrymentioning
confidence: 99%
“…Wind stress as a driver of sea level change Many studies have been conducted on the underlying mechanism that connects the changes in external forcing to the sea level, using a range of models, and focusing on different regions. For instance, in the Indian and Pacific Oceans it was shown that DSL change is mainly driven by wind stress, using either a simplified dynamical ocean model (Timmermann et al 2010) or an ocean general circulation model (Nidheesh et al 2013). In addition, Piecuch andPonte (2011, 2012) pointed out that buoyancy forcing is important to explain interannual variability in sea level in both the tropical Atlantic and the tropical Pacific regions.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies suggest that over the past few decades change in wind forcing is the main cause for decadal sea level variability in the Pacific, including the intensified SLR in the western tropical Pacific since the early 1990s (e.g., Qiu 2002;Carton et al 2005;Bindoff et al 2007;Köhl et al 2007;Köhl and Stammer 2008;Roemmich et al 2007;Timmermann et al 2010;Merrifield and Maltrud 2011;McGregor et al 2012;Nidheesh et al 2013;Qiu and Chen 2012;Han et al 2014a). Given that a significant portion of the basinscale coherent sea level pattern is associated with the PDO and NPGO, one can conclude that it is the surface wind changes associated with the PDO and NPGO that are the major cause for the basin-wide sea level patterns.…”
Section: Forcing and Processesmentioning
confidence: 99%
“…2,3,6), model experiments that use the extracted winds as surface forcing to quantify the roles played by the PDO and NPGO have not yet been performed. Moreover, the regression method may not cleanly isolate the wind signals associated with the climate modes (Palanisamy et al 2015), and reanalysis winds that were used in the regression analyses have significant uncertainties (e.g., Wittenberg 2004), with apparent discrepancies or even opposite signs in their multidecadal trends since the 1960s (Nidheesh et al 2013). Yet, reanalysis winds have been widely applied to investigate decadal climate variability due to their longer data records than satellite winds, and decadal trends of sea level over tropical oceans are very sensitive to the wind trends (McGregor et al 2012).…”
Section: Forcing and Processesmentioning
confidence: 99%